2022
DOI: 10.1002/sdtp.15683
|View full text |Cite
|
Sign up to set email alerts
|

P‐8: Analysis of Degradation Mechanism of Oxide Semiconductor FETs with High Tolerance to Intense NBTIS

Abstract: This work verifies the existence of more than one cause of NBTIS degradation of oxide semiconductor FETs by analyzing its time dependence. As defects in a gate insulator (GI) that cause NBTIS degradation, indium diffused into the GI also serves as hole trap defects besides the NBOHC defects proposed by Tsubuku et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The VFET demonstrated remarkable stability, as evidenced by the V th shift measurements taken during tests at 60 C and at gate-source voltages (V gs ) of ±20 V for a duration of 3600 s. Our previous investigations into NBTIS degradation mechanisms have confirmed that FETs incorporating CAAC-OS active layers are less susceptible to NBTIS degradation due to low light absorption coefficients of the OSs and fewer numbers of holes injected into the GI. 25,26 This evidence strongly suggests that the employment of CAAC-OS active layers renders VFETs highly resistant to NBTIS degradation.…”
Section: Evaluation Of Vfet Reliabilitymentioning
confidence: 92%
“…The VFET demonstrated remarkable stability, as evidenced by the V th shift measurements taken during tests at 60 C and at gate-source voltages (V gs ) of ±20 V for a duration of 3600 s. Our previous investigations into NBTIS degradation mechanisms have confirmed that FETs incorporating CAAC-OS active layers are less susceptible to NBTIS degradation due to low light absorption coefficients of the OSs and fewer numbers of holes injected into the GI. 25,26 This evidence strongly suggests that the employment of CAAC-OS active layers renders VFETs highly resistant to NBTIS degradation.…”
Section: Evaluation Of Vfet Reliabilitymentioning
confidence: 92%
“…Recently, Hosaka et al reported that cations can diffuse from the active layer into an insulator via the thermal budget, which may hinder our experiments. 31 Therefore, to understand the relationship between the diffusion of cations and variations in V O , we performed a TEM-EDS analysis of the stacked film. Figure 2a shows the cross-sectional TEM images and EDS line scan of the stacked film before and after annealing at 600 °C.…”
Section: Understanding the Impact Of Annealing Temperatures On The Al...mentioning
confidence: 99%